2003
DOI: 10.1080/13550280390194046
|View full text |Cite
|
Sign up to set email alerts
|

Virus Demyelination

Abstract: A number of viruses can initiate central nervous system (CNS) diseases that include demyelination as a major feature of neuropathology. In humans, the most prominent demyelinating diseases are progressive multifocal leukoencephalopathy, caused by JC papovirus destruction of oligodendrocytes, and subacute sclerosing panencephalitis, an invariably fatal childhood disease caused by persistent measles virus. The most common neurological disease of young adults in the developed world, multiple sclerosis, is also ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 194 publications
1
44
0
Order By: Relevance
“…8 Several viruses can cause diseases involving demyelination, including measles, human immunodeficiency virus (HIV), and the human T-cell lymphotropic virus type I. 23 Therefore, it is biologically plausible for MS, as a demyelinating disease, to have a viral etiology. Viruses associated with MS have included measles, 3 Epstein-Barr virus (infectious mononucleosis), 4 human herpes virus 6, 5 and mumps.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several viruses can cause diseases involving demyelination, including measles, human immunodeficiency virus (HIV), and the human T-cell lymphotropic virus type I. 23 Therefore, it is biologically plausible for MS, as a demyelinating disease, to have a viral etiology. Viruses associated with MS have included measles, 3 Epstein-Barr virus (infectious mononucleosis), 4 human herpes virus 6, 5 and mumps.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these DEGs remained downregulated long after virus replication had ended, suggesting that SVV infection of the ganglia results in long-term changes in the ganglion transcriptome. Several of these genes were involved in myelination (MOBP, MAG, MBP, and PRG4), which suggested that SVV may lead to demyelination, as has been described for HSV-1 and -2 (149,150). Genes downregulated 14 dpi were involved in neuronal apoptosis, which may be another strategy that SVV utilizes to establish latency in the ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Immune mediators secreted by T cells and macrophages/microglia have been suggested to contribute to virally-induced demyelination due to dysregulation or death of oligodendrocyte lineage cells (Marro et al, 2014). These models are often considered alongside autoimmune-based models such as EAE, as they are useful for the characterization of infectious events leading to CNS immune responses (Baker and Amor, 2015; Fazakerley and Walker, 2003). Although EAE is powerful and remains most commonly used MS model, it is recognized that its limitations for MS therapy (Constantinescu et al, 2011) stem from a dependence on the artificial induction of the immune response (Mecha et al, 2013), unreliable predictability of treatments, a spinal cord preference over brain lesions, difficulty in analyzing remyelination of stochastic lesions and inconsistency of clinical functional progression (Ransohoff, 2012).…”
Section: Introductionmentioning
confidence: 99%